Efficacy of scaffold‐mediated localized chemotherapy in cancer: A systematic review of current research. (3rd March 2020) - Gupta, Archana A; Kheur, Supriya; Arakeri, Gururaj; Thirumal Raj, A; Badhe, Ravindra V.; Patil, Shankargouda; Rao US, Vishal; Patil, Shekhar; Gomez, Ricardo S.; Thomson, Peter; Brennan, Peter A
Abstract: Objective: To assess the efficacy of scaffold‐mediated localized chemotherapy in cancer. Methods: Databases including PubMed, Cochrane Library, and SCOPUS were searched for articles reporting the use of scaffold‐mediated localized drug delivery in cancer. Essential data including scaffold fabrication material and methods, drug dosage and release duration and its effect on the cancer cells were extracted. Results: 15 articles out of 60 screened, fulfilled the eligibility criteria. Among the 15 studies, 5 studies included only cell lines and 2 studies were on mouse models, while 8 studies involved a combination of cell lines and mouse models. Scaffold materials included both synthetic polymers such as poly‐lactide, polycaprolactone and natural materials including d‐periosteum and human micro‐fragmented adipose tissueA wide number of other variables included the fabrication procedure, drugs used, and the methods used to assess the effects on cancer. As a result, it was not possible to make any direct comparison of the efficacy of the therapeutic strategy used in each of these studies. Conclusion: Irrespective of the many variables, a common consensus in all the included studies was that scaffold mediated localized drug delivery effectively reduced cancer cell viability by increasing drug bioavailability to the target tissue, while its localized effect reduced the risk of systemic toxicity.